1998
DOI: 10.4141/a97-101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed and dietary energy content within breed on growth performance, carcass and chemical composition and beef quality in Hereford and Simmental steers

Abstract: . 1998. Effects of breed and dietary energy content within breed on growth performance, carcass and chemical composition and beef quality in Hereford and Simmental steers. Can. J. Anim. Sci. 78: 533-541. Forty-eight Hereford and 60 Simmental steers were used to evaluate breed differences as affected by dietary energy content on growth performance, carcass and chemical composition, and beef quality. Diets were based on corn silage, alfalfa haylage, whole corn, and SBM and were formulated to provide 2.52 to 2.81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
6
11
1
2
Order By: Relevance
“…HE had ) differ significantly (P < 0.05) + not examined due to presence of breed by year interaction 1 evaluated only in year 2 (Scale 1 = S (best) to 6 = P (poorest)) 2 evaluated only in year 2 (Scale 1 (leanest) to 5 (fattest)) *adjusted means (slaughter weight used as a covariate) **LS means (no covariate used) the lowest, SI intermediate, and AA and CH bulls the highest percentage of bones and tendons. Similar to the present study, no significant differences were found between bone yields of SI and HE bulls and steers (Mandell et al, 1997(Mandell et al, , 1998 and SI and Red Angus steers (Laborde et al, 2001). Meat to bones and tendons ratios reflected the relationships between the two components in carcasses from different groups.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…HE had ) differ significantly (P < 0.05) + not examined due to presence of breed by year interaction 1 evaluated only in year 2 (Scale 1 = S (best) to 6 = P (poorest)) 2 evaluated only in year 2 (Scale 1 (leanest) to 5 (fattest)) *adjusted means (slaughter weight used as a covariate) **LS means (no covariate used) the lowest, SI intermediate, and AA and CH bulls the highest percentage of bones and tendons. Similar to the present study, no significant differences were found between bone yields of SI and HE bulls and steers (Mandell et al, 1997(Mandell et al, , 1998 and SI and Red Angus steers (Laborde et al, 2001). Meat to bones and tendons ratios reflected the relationships between the two components in carcasses from different groups.…”
Section: Resultssupporting
confidence: 89%
“…Similarly to our findings, SI and CH steers had higher average daily gains than all the other compared breed groups (including AA and HE) after a constant time on feed (Gregory et al, 1991(Gregory et al, , 1994a. On the contrary, medium framed HE steers gained more than large framed SI steers when fed to a common backfat endpoint presumably due to a shorter time on feed and higher efficiency for maintenance and gain (Mandell et al, 1998). Similarly, Chambaz et al (2001) reported higher gains of AA compared to SI and CH slaughtered at a common target level of intramuscular fat also probably resulting from lower age at slaughter and days of fattening in AA.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In agreement with our study, the average live weight gain and feed efficiency were positively affected by a higher dietary energy concentration in Simmental bulls (Sami et al, 2004). Also, increasing the dietary energy content improved daily live weight gains and feed efficiency in Simmental and Hereford steers (Mandell et al, 1998). Replacing grass silage with maize silage improved the growth rate and feed conversion efficiency of Simmental × Holstein steers, as reported by Juniper et al (2005).…”
Section: Discussionsupporting
confidence: 90%